Sri Lanka : Investment in Human Capital - World Bank (Washington, DC, 2014)
Education is one of the most important determinants of economic performance in the modern world. This is true of both countries and individuals. The main characteristic which distinguishes between advanced economies, middle-income economies and low-income countries, is the knowledge content of their production activities and processes. Economic activities and products have become increasingly knowledge and skill-intensive in recent years. In addition, the importance of knowledge and skills is growing at an accelerating pace. Education is at the heart of human capital accumulation and economic growth. Education increases cognitive skills and soft skills of individuals. In addition, education improves the capacity of individuals to be trained for specific occupations and to acquire job-related skills. These effects of education enable individuals to accumulate human capital, improve labor productivity and increase life-cycle earnings. In the aggregate, this process generates economic growth. Investment in education produces a broad range of social benefits. Well-educated individuals, especially women, are better able to control their fertility and family health, resulting in reduced child, infant and maternal mortality, and higher life expectancy. Education also facilitates social mobility by creating opportunities for poor and disadvantaged groups to raise their economic and social status. A broad range of further externality benefits of education have been identified in the economic literature. These cover aspects of social well-being such as better political decision making, reduced incidence of crime, and higher quality public services. Education also produces inter-generational economic and social benefits: increased education in one generation improves schooling, labor productivity and income in the next. The public goods, informational imperfections and distributive justice aspects of education provide the economic justification for state investment in the education sector.